4X-4-6x-10=-3x-1

Simple and best practice solution for 4X-4-6x-10=-3x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4X-4-6x-10=-3x-1 equation:


Simplifying
4X + -4 + -6x + -10 = -3x + -1

Reorder the terms:
-4 + -10 + 4X + -6x = -3x + -1

Combine like terms: -4 + -10 = -14
-14 + 4X + -6x = -3x + -1

Reorder the terms:
-14 + 4X + -6x = -1 + -3x

Solving
-14 + 4X + -6x = -1 + -3x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 4X + 14 + -6x = -1 + 14 + -3x

Reorder the terms:
-14 + 14 + 4X + -6x = -1 + 14 + -3x

Combine like terms: -14 + 14 = 0
0 + 4X + -6x = -1 + 14 + -3x
4X + -6x = -1 + 14 + -3x

Combine like terms: -1 + 14 = 13
4X + -6x = 13 + -3x

Add '6x' to each side of the equation.
4X + -6x + 6x = 13 + -3x + 6x

Combine like terms: -6x + 6x = 0
4X + 0 = 13 + -3x + 6x
4X = 13 + -3x + 6x

Combine like terms: -3x + 6x = 3x
4X = 13 + 3x

Divide each side by '4'.
X = 3.25 + 0.75x

Simplifying
X = 3.25 + 0.75x

See similar equations:

| 2(x+1)-5=25 | | 2/3=5/6 | | 11x-5=45 | | -2/3=5/6 | | 4-(6+5)=3(6-11) | | 4(3x-2)-5x= | | x/4.91*6-1.4=3 | | 6cosx-4=0 | | x-3/10=5/10 | | 5y+18=-y-6 | | 120=x(x^2/20) | | 14x+5=-7+19x | | 3(x-5)+2(3x+11)=45 | | 3(2r-3)=0.2r+0.9 | | 12+6y=-8y-2 | | 5x^2+16+3=0 | | -3(4x+3)+4(6x+1)=41 | | 2x+17=8(x-1)+1 | | y=0.5x+0.5 | | -17-2x=16-x | | (9a^-6b^2)/(17a^6b^-8) | | 1/3y+1/4=15/12-1/4 | | 3/4x7/12= | | 9x^2+4x-81=0 | | 3xsquared+11x=4 | | -4+.666y=.5y-5 | | 8/93/21 | | x=3x-127 | | 20=q | | 0.14y-1.6+3.12y+3.6= | | -6-3(2k-4)=18 | | a/3=-0.2 |

Equations solver categories